Simulation of host of distributed computer integrated manufacture - Тарасова, Анна Владимировна (Eastern-European Journal of Enterprise Technologies, 2012)
This article discusses the use of microcontrollers as a host of distributed computer integrated manufacture. Simulation model of host is proposed for the design and analysis. The results obtained during the full-scale and software simulation are shown in the article